Current limiting tests of a prototype 160 kV/1 kA resistive DC superconducting fault current limiter. (17th November 2020) - Song, Meng; Sheng, Chao; Ma, Tao; Huang, Yong; Yang, Chao; Xin, Ying; Jin, Hui; Yang, Tianhui; Xiong, Jialing; Li, Chao; Li, Quan; Wang, Changqi; et al.
Abstract: High voltage direct current (HVDC) transmission technology has begun to play a great role in power transmission industry over the last decade. However, short-circuit fault seriously threatens the safety of an HVDC network. In order to reduce the fault current level of an HVDC network, utilizing a superconducting fault current limiter (SFCL) was proposed by researchers and engineers worldwide. Recently, Guangdong Grid Company of China Southern Power Grid, Co. has led a project to develop a 160 kV/1 kA resistive type DC SFCL. As a middle-step objective, a 160 kV/1 kA laboratory prototype has been developed. Due to a facility with an adequate capacity for testing such DC equipment is practically inaccessible, the current limiting performance of the prototype cannot be tested with a straightforward current limiting experiment. In practice, effectual alternative methods have to be adopted. Since the AC half-wave impact method requires less equipment and cost than the DC impact method, we took on an AC half wave impact current method to evaluate the current limiting function of the prototype alternatively. In this paper, we report the procedures and results of these tests.